Dental eruption sequence and hypsodonty index of a Pleistocene macraucheniid from the Brazilian Intertropical Region. (14th August 2017) - Souza Lobo, Leonardo; Lessa, Gisele; Cartelle, Cástor; Romano, Pedro S. R.
Abstract: Litopterna is represented in the Pleistocene of the Brazilian Intertropical Region by a monospecific genus of Macraucheniidae, Xenorhinotherium . Although most of the knowledge about this family is derived from the dentition, some dental features still remain unknown. This study describes the eruption sequence of permanent dentition and classifies the hypsodonty status of X . bahiense . The specimens studied are from Toca dos Ossos, a limestone cave located in Bahia State. We perform qualitative macroscopic analysis to describe the eruption dental sequence. Additionally, we perform quantitative analysis to determine the hypsodonty index. The dental eruption sequence of the juvenile specimen is M1, M2, I1, I2, M3, I3, P1, P2, P3, and P4. In addition, the analysis of tooth wear in adult specimens provides similar results. The hypsodonty index assigns a mesodont tooth crown for X . bahiense . The dental eruption sequence is most similar to a rapid-growth extant mammal. Moreover, our results do not support afrotherian-like delayed dental eruption to Litopterna. The hypsodonty index can be related to data on vegetation of the Brazilian Intertropical Region and the shape of the premaxilla of X . bahiense, both of which suggest a browsing diet for this macraucheniid.